Schizophrenia and Oral Health - Review of the Literature - Đorđević Vladan; Dejanović Slavica Đukić; Janković Ljiljana; Todorović Ljubomir (Balkan Stomatological Society, 2016)
Patients with schizophrenia, especially during period of their hospitalization, are likely to constitute a high-risk group of individuals with respect to prevalence of oral diseases. Several factors are mentioned in the manuscript that may contribute to the finding of increased prevalence of oral diseases in patients with schizophrenia. Unfortunately, some of these can be attributed to dental profession; these patients are sometimes deprived of dental service as they cannot afford the treatment due to its cost and they are even neglected sometimes by dental professionals. The idea of providing oral health care in the environment of specialized health care institutions, such as psychiatric hospitals, during periods of hospitalization, is especially emphasized.